Recommendations for the prevention of surgical site infections and use of antibiotic therapy during preoperative nursing care in surgery departments - Szewczyk, Maria T.; Cwajda-Białasik, Justyna; Mościcka, Paulina; Jawień, Arkadiusz; Gospodarek, Eugenia; Deptuła, Aleksander; Kózka, Maria; Szopiński, Jacek; Mikucka, Agnieszka; Cierzniakowska, Katarzyna; Fórmankiewicz, Bartosz; Popow, Aleksandra; et al. (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2015)
Poland lacks uniform national guidelines for the prevention of surgical site infections (SSI) in the area of perioperative antibiotic and nursing care. Key criteria for effective SSI prevention are included in the current CDC recommendations. The present document contains a total of 13 recommendations that aim to organize scientific data collected to date, and address activities undertaken primarily by surgical nurses with respect to SSI prevention. The recommendations apply to the preoperative period.